The influence of the environment in the conception of the speech: an analysis from the synthetic junction - Hernández Patrón, Úrsula (2019)
The purpose of this study is to demonstrate the important effect that the medium has on the features of the linguistic products, which differs from de proposal made by Koch and Oesterreicher in their text lengua hablada en la Romania: español, francés, italiano (2007). This demonstration will be achieved from the analysis of the most frequently used junction techniques, proposed by Raible (2001:1992), in the news published in the digital versión of the peruvian newspaper El Comercio, specifically those that were initially manifested by the phonic medium and then passed to the graphic médium. To achieve that, we considered news that present audiovisual material with their respective written material. The junction techniques will be presented and analyzed from an illustrative sample to identify how are these mechanisms used when the news were transferred from one medium to the other. The results show that the junction techniques areregularly used by the writers in their texts with the purpose of uniting clauses, wich shows that the medium is important to define the concept of a text.